1995
DOI: 10.1007/bf02368395
|View full text |Cite
|
Sign up to set email alerts
|

How to overcome osmotic stress? Marine crabs conquer freshwater. New insights from modern electrophysiology

Abstract: In the present article we review our findings on split lamella preparations of crab gills mounted in modified Ussing-chambers with respect to mechanistic and ecophysiological aspects. The leaky gill epithelium of shore crabs adapted to brackish water absorbs Na + and C1-in a coupled mode, and shows similarities to other salt-absorbing epithelia exposed to moderately diluted media. The results so far obtained for NaCI uptake across the gills of the shore crab are compatible with a transport model where two cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…On the other hand, the Gte increase at increased Isc after also reducing the osmolarity (but at constant ionic strength) indicates a change in the transcellular conductance. In many epithelia, including crab gills (Onken et al, 1991(Onken et al, , 1995, the apical membrane is, by far, the barrier of highest resistance along the transcellular pathway, and significant conductance changes are most likely due to modulations in this membrane. Thus, it seems likely that the Gte increase in the presence of Hyposmotic saline is related to the modulation of an apical, electrogenic transporter.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Gte increase at increased Isc after also reducing the osmolarity (but at constant ionic strength) indicates a change in the transcellular conductance. In many epithelia, including crab gills (Onken et al, 1991(Onken et al, , 1995, the apical membrane is, by far, the barrier of highest resistance along the transcellular pathway, and significant conductance changes are most likely due to modulations in this membrane. Thus, it seems likely that the Gte increase in the presence of Hyposmotic saline is related to the modulation of an apical, electrogenic transporter.…”
Section: Discussionmentioning
confidence: 99%
“…This channel has a high permeability to chloride ions, but it is not known whether it is encoded by the parasite genome (10). Interestingly, vacuolar H ϩ -ATPases (V-H ϩ -ATPases) 3 are associated with chloride channels in the plasma membrane of numerous cells (11)(12)(13)(14)(15), and some stages of malaria parasites selectively invade V-H ϩ -ATPase-containing cells (16). Normal erythrocytes, however, do not possess a V-H ϩ -ATPase.…”
mentioning
confidence: 99%
“…Due to the necessity of inward C1-transport in tap water, the increase of CA activity seems to be a response to the external low C1-concentration. But here some contradictions arise: In E. sinensis, the results derived from electrophysiological and biochemical investigations indicated that electrogenic C1-transport depends on the cooperation of a proton pump and the CA (Onken et al, 1995). In contrast, experiments on C. maenas concerning potential difference, fluxes of Na + and C1- (B6ttcher et al, 1991) and short circuit current experiments (Onken & Siebers, 1992) do not reveal any participation of CA activity in Na+/C1 -transport.…”
Section: Effects Of Acclimation From Tap To Salt Watermentioning
confidence: 97%